A Heatmap for Monitoring Systemic Risk in Norway - Elif Ceren Arbatli; Rønnaug Melle Johansen (Norges Bank, 2017)
We develop a tool to monitor systemic risk in Norway's financial system. In particular, we construct 39 indicators capturing a wide range of financial vulnerabilities and organise them under three broad classes of vulnerabilities: risk appetite and asset valuations, non-financial sector imbalances and financial sector vulnerabilities. We track their evolution over time using ribbon heatmaps and construct summary indicators. By including a broad set of indicators, the heatmap is better able to capture the complex set of factors that are associated with the financial cycle and a wide range of risks and vulnerabilities. The heatmap signals the build-up of risks in the Norwegian financial system leading up to the banking crisis in Norway (1988-93) and the financial crisis (2008-09). Furthermore, an analysis of the relationship between different components of the heatmap suggests that increases in risk appetite and asset valuations tend to foreshadow increases in imbalances in the non-financial sector, as well as higher leverage and exposure to funding risks in the banking system. Several heatmap indicators also tend to lead standard measures of imbalances used by policymakers such as the credit-to-GDP gap. Providing early and broad-based signals of risks, the heatmap can therefore serve as a useful input for macroprudential policy.
hdl:11250/2506371
Keywords: 330